The same yet different? Teaching quality differs across a teacher's classes, but teachers with higher knowledge make teaching quality more similar. (August 2022) - Voss, Thamar; Zachrich, Lisa; Fauth, Benjamin; Wittwer, Jörg
Abstract: Teachers usually teach different classes. We examined the extent to which teaching quality varied across a teacher's classes and the extent to which it was influenced by a teacher's knowledge. We applied three-level models (levels: student, class, and teacher) to our data on 210 beginning teachers. Students from up to five classes per teacher rated the teaching quality with regard to cognitive activation, student support, classroom disturbances, and monitoring. We found that teaching quality varied substantially across a teacher's classes. Furthermore, teachers with higher pedagogical/psychological knowledge exhibited higher teaching quality and, to some extent, lower variability in teaching quality across their classes. Thus, teachers' pedagogical/psychological knowledge seems to be important for achieving high average teaching quality and for adopting to different classroom contexts. As a substantial proportion of the variance across a teacher's classes cannot be explained by teachers' knowledge, we discuss the need for research on other influencing factors. Highlights: Teachers with higher professional knowledge exhibit higher average teaching quality. Teaching quality varies substantially across a teacher's classes. Teacher knowledge contributes to making teaching quality across classes more similar.